Virtual anatomical reconstruction of large acetabular bone defects using a statistical shape model. Issue 6 (26th April 2017) - Vanden Berghe, Peter; Demol, Jan; Gelaude, Frederik; Vander Sloten, Jos
Abstract : Custom implants are used to treat patients with large acetabular bone defects. To quantify the bone defect and to initialize the implant design, a virtual anatomical reconstruction of the bone needs to be performed. Our SSM-based reconstruction approach was used to overcome the limitations of the mirrored contralateral method and improves upon other SSM reconstruction techniques. The reconstruction errors for the acetabular direction, the hip joint center and the acetabular radius were, respectively:, 2.6 mm and 0.7 mm. We believe that our method can be an essential tool in the planning and the design of custom implants.